Economic cost of vaccine hesitancy and refusal in Zambia: a systematic review - Joseph C. Mulenga (Discover Global Society)
Abstract Introduction Vaccine hesitancy has been identified as one of the top 10 threats to global health. Trust in the manufacturing companies and safety of drugs have recently emerged as the predominant reasons people are hesitant to get vaccines. This is despite vaccines effectively curtailing disease outbreaks for centuries. While the public health benefits of vaccines are widely recognized, the economic impact of vaccine hesitancy and refusal in Zambia is not well established. This study attempts to provide highlights of the economic impact of vaccine hesitancy and refusal in Zambia with the hope of improving vaccine uptake by the general public as well as forming the basis for developing and enforcing the already existing policies that treat vaccine hesitancy not only as a medical concern but also as an economic threat. Aim The study endeavour to ascertain the economic impact of vaccine hesitancy in Zambia. Methodology A systemic review of literature was done by searching for relevant studies published in various databases (PubMed and Google scholar). Those missed but relevant were captured by snowball method. Selection of the identified articles was done according to PRISMA 2020 statement. Additional data was extracted from the Central Statistics Office (CSO) and the Zambia National Public Health Institute (ZNPHI) websites to provide the local context. CASP Checklist was used to ensure that only quality articles are reported on. For data extraction, thematic data analysis was used to capture the information used to form the narrative. Results Nine studies were included to form the narrative. Five studies analysed the economic impact of vaccine hesitancy on COVID- 19 vaccines while 4 analysed other vaccines which included measles containing vaccines (MCV), Bacillus Calmette-Guerin (BCG), oral cholera vaccines (OCV) and diphtheria pertussis and tetanus vaccine (DPT). This include studies done in Zambia (N = 7) and those that were part of the regional studies with a particular focus on Zambia (N = 2). These studies showed that the most remarkable economic costs of vaccine hesitancy are loss of human capital through death, increased direct and indirect medical costs, vaccine wastage due to low uptake and loss of businesses especially during lockdowns. Conclusion This systematic review highlights the economic costs associated with vaccine hesitancy in Zambia. It demonstrates that the impact of hesitancy or refusal extends beyond the public health concerns to include economic effects at both the household and national levels. Further economic evaluations using meta-analysis could provide a more precise quantification of these impacts for specific vaccines.